Clearly Crisp, and Not Fuzzy: A Reassessment of the (Putative) Pitfalls of Multi-value QCA. Issue 2 (May 2013) - Thiem, Alrik
In a recent contribution to this journal, Vink and van Vliet seek to raise researchers' awareness of the potentials and pitfalls of multi-value Qualitative Comparative Analysis (MvQCA). The authors are unconvinced by the technique's distinctness from the more established crisp-set QCA (csQCA) and fuzzy-set QCA (fsQCA) variants and question its added value to configurational comparative methodology on five points. This article demonstrates why none of them challenges mvQCA. Two points do not relate to the method, two are based on incorrect reasoning, and one results from a misunderstanding of notational systems. This comment seeks to prove the suspicion against mvQCA that has prevailed thus far in the literature unjustified. It argues that this variant is as useful a contribution to the toolbox of comparative social science methodology as csQCA and fsQCA.